OS07.1.A A threshold of mitotic activity and post-surgery residual volume are independant prognostic factors in astrocytoma IDH-mutant. (5th September 2022) - Tran, S; Thomas, A; Touat, M; Karachi, C; Lozano, F; Mokhtari, K; Dehais, C; Feuvret, L; Carpentier, C; Giry, M; Doukani, H; Lerond, J; et al.
Abstract: Background: The distinction between grade 2 and 3 is instrumental to choose between observational follow-up and adjuvant treatment in resected astrocytoma IDH-mutant. However, criteria of grade 2 versus 3 have not been updated since the WHO 2007 classification. There is no consensus on the method of evaluation of the mitotic activity or a cut-off of mitoses separating grade 2 and grade 3 tumors. The objectives were to evaluate the maximal mitotic activity on a series of resected astrocytoma IDH-mutant and assess its prognostic impact on survival. Material and Methods: Maximal mitotic activity on consecutive high power fields corresponding to 3 mm 2 was examined in 118 lower-grade astrocytoma IDH-mutant. The prognostic value for time-to-treatment (TTT) and overall survival (OS) of mitotic activity and other putative prognostic factors (including age, performance status, pre-surgical tumor volume, plurilobar involvement, post-surgical residual tumor volume, midline involvement) was assessed in tumors with (i) ATRX loss, and (ii) without CDKN2A homozygous deletion, lesional enhancement, histological necrosis nor microvascular proliferation. Results: Among the 75 (64%) of tumors which had gone through observational follow-up after resection, the maximal mitotic activity, the post-surgical residual volume and the plurilobar involvement were independent prognostic factors of TTT (p < 0.0001). A threshold of mitotic activity for grade 2 was fitted on TTT and OS prognosis. Using this threshold, patients with "grade 2 tumors" had a median TTT of 55 months versus 19 months for "grade 3" (p = 0.0057) and a median OS of 102 months versus 73 months respectively (p = 0.001). Residual volume < 1 cm 3 was associated with longer OS (113 months versus 88 months, p = 0.0021). Conclusion: Mitotic activity and post-surgical residual volume can be combined to evaluate prognosis in resected astrocytoma IDH-mutant and could select the best candidates for observational follow-up.